1998
DOI: 10.1111/j.1399-6576.1998.tb05318.x
|View full text |Cite
|
Sign up to set email alerts
|

Postural post‐dural puncture headache after spinal and epidural anaesthesia. A randomised, double‐blind study

Abstract: SA gave more headache but superior quality of surgical anaesthesia compared with EA. Dural puncture, and not expectation, is the major cause of PPDPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
2
16
0
1
Order By: Relevance
“…The results in this study are correlated with the previous studies focusing over the same issue [5,[8][9][10][11][12][13] this is the first study analyzing this issue in the middle east or Egypt, it will add to the data base regarding the developing countries and focus on the patient traditions, economics and suffer [5,13].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The results in this study are correlated with the previous studies focusing over the same issue [5,[8][9][10][11][12][13] this is the first study analyzing this issue in the middle east or Egypt, it will add to the data base regarding the developing countries and focus on the patient traditions, economics and suffer [5,13].…”
Section: Discussionsupporting
confidence: 73%
“…The lateral bevel orientation or the expert anesthetist achieving the block from the first shot was not enough to reduce the PDPH incidence in the G22 or G20 needle [8,12].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,10,11 In this study, the overall incidence of PDPH was 8.3%, which is comparable to the findings of previous anaesthetists who used cutting needles in obstetric patients. 9,12 To the best of our knowledge, this is the first report of obstetric spinal anaesthesia and PDPH from West-Africa, where Quincke needles are used by most anaesthetists. Our results agree with previous reports that there is a positive correlation between spinal needle size and the incidence of PDPH.…”
Section: Discussionmentioning
confidence: 94%
“…PDPH is believed to be caused by leakage of CSF from the iatrogenic hole made in the dura mater following diagnostic lumbar puncture, spinal anaesthesia or accidental dura puncture during epidural anesthesia. 2,5,9 This CSF loss leads to a low-pressure headache syndrome that may be severe enough to interfere with the patient's activities of daily living. Previous studies have shown a positive correlation between the size and configuration of the hole in the dura and the incidence of PDPH.…”
Section: Discussionmentioning
confidence: 98%